A high pressure die cast magnesium alloy with superior thermal conductivity and high strength. (December 2021) - Rong, Jian; Zhu, Jia-Ning; Xiao, Wenlong; Zhao, Xinqing; Ma, Chaoli
Abstract: Thermal conductivity is a key parameter for high performance material needed for electronic devices. While most commercially used Mg foundry alloys exhibit low thermal conductivities. In this work, we developed an Mg–3RE–0.5Zn alloy that is suitable for high pressure die cast (HPDC) ultrathin wall cellphone components. The thermal conductivity of this alloy was measured to be 133.9 W/(m·K) at room temperature, approximately 85% that of pure Mg (156 W/(m·K)). Meanwhile, it exhibited acceptable room-temperature mechanical properties with high yield strength of ∼153 MPa, ultimate tensile strength of ∼195 MPa, and elongation of ∼4.3%. The excellent combination of superior thermal conductivity and high strength is attributed to low solute atoms in the α-Mg matrix and the formation of networked (Mg, Zn)12 RE eutectic phase. The results from this study will be helpful for developing new HPDC Mg alloys with more excellent performances and promoting the wider application of Mg alloys. Highlights: ● A Mg–3RE–0.5Zn alloy with superior thermal conductivity and high strength for ultrathin-walled cellphone components was successfully developed via high pressure die casting (HPDC). ● The solute atoms in the α-Mg matrix were almost fully consumed by the formation of the continuous networked Mg12 RE intermetallic phase, leading to the high thermal conductivity (133.9 W/(m·K)). ● The networked Mg12 RE intermetallic phase and fine grain structure (∼4.3 μm) accounted for the high strength of the HPDC alloy.